PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) MATEMATIKA MATERI HIMPUNAN BERBASIS REALISTIC MATHEMATICS EDUCATION (RME) KELAS VII SMP NEGERI 4 PADANG - RIVOL YULIAN PUTRA (Departemen Matematika, 2021)
Student worksheets are supporting materials for learning mathematics learning that are needed by teacher to achieve learning objectives. However, found in the field shows that learning mathematics is still classified as learning that students do not like beacuse the teaching materials provided by teacher are not attractive to students. Thisoiresearch aims to develop student worksheets that can attract student to prefer learning mathematics. This type of research is a development based on Realistic Mathematics Education with the Plomp method which consisits of a preliminary research stage and a prototyping phase. The preliminary research stage includes needs analysis, student analysis, curriculum analysis and concept analysis. The prototyping phase is the stage for designing teaching materials which consists of 3 prototypes. The result showed that the teaching materials produced were valid and practics. Keywords – Student Worksheets, mathematics learning, RME